Role of α 2- Heremans and Schmid glycoproteins (α 2-HSG) as a threshold concept of calcification in patients with Chronic Kidney Disease - Jawad, Rashad R; Nidah, Shaimaa Z; Hameed, Rana M; Makki, 4Mohammed M (International Journal of Psychosocial Rehabilitation, 2020)
Fetuin A (FA, AHSG or a 2-HS glycoprotein) is a glycoprotein mainly produced by liver. FA can inhibit the de novo formation and precipitation of the apatite precursor mineral (namely calcium phosphate). Therefore, FA can prevent undesirable calcification in the circulation without inhibiting bone mineralization.Cardiovascular disease (CVD) in chronic kidney disease (CKD) is explained in part by traditional cardiovascular risk factors; by uremia-specific factors, abnormalities of mineral metabolism, and the vascular calcification process. Lower serum concentrations of FA was independently associated with risk of cardiovascular. The main aims of the study were to follow the role of FA in the progression of renal disease which promoted cardiovascular disease. Improving the understanding of the mechanisms of action might undoubtedly lead to well therapies to combat the destructive effects in CKD.The present work included a cross sectional study for a group of 80 subject patients with end stage chronic kidney disease were selected from hemodialysis unit at the Nephrology Department, Al Hussein Teaching medical city. Blood samples were collected from dialysis unit from fistule pre heparinized, pre dialysed patients. Enzyme Link Immunosorbat Assay system (ELISA) was performed using Sandawich method to measure the concentrations of serum Human Fetuin A and Parathyriod hormone (PTH). Significant differences in continuous variables among the parameters were confirmed through analytical statistical tests.Associations of characteristic parameters with serum Fetuin A levels were shown high significant difference specially with Creatinine, Urea, K, increased levels of these parameters were significantly associated with decreased FA levels (P<0.001), while ; in spite of the normal range of (Na, Ca, P and Albumin) levels, there was a significantly associated with decreased FA levels (P<0.001). Analysis of correlation illustrated that FA has a positive relationship with Hb, serum Albumin levels and serum K levels (P<0.001), while inverse and significant correlations of FA was manifested with serum Urea, Creatinine , Phosphorous l, Na, Ca levels, all have (P<0.001).In CKD patients, FA levels were decreased. Serum concentrations of FA were decreased in patients with end stage renal disease on dialysis, and lower serum concentrations were independently associated with risk of cardiovascular (vascular calcification) which increase the mortality in this population, fetuin A was strongly independent prognostic factor of the severity of CVD.